2017
DOI: 10.1038/pr.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status is associated with treatment failure and duration of illness in Nepalese children with severe pneumonia

Abstract: BACKGROUND: There is no consensus on optimal Vitamin D status. The objective of this study was to estimate the extent to which vitamin D status predicts illness duration and treatment failure in children with severe pneumonia by using different cutoffs for vitamin D concentration. METHODS:We measured the plasma concentration of 25(OH)D in 568 children hospitalized with World Health Organization-defined severe pneumonia. The associations between vitamin D status, using the most frequently used cutoffs for vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 37 publications
(43 reference statements)
2
20
0
12
Order By: Relevance
“…Low vitamin D status is an independent risk factor for treatment failure and delayed recovery from severe lower respiratory infections. 52 The level of serum vitamin D in patients with pneumonia was significantly low, 53 maybe because of a systemic inflammatory response in the host. 54,55 In total, there remains little evidence to suggest that vitamin D supplementation has an effect on most outcomes, including time to resolution of pneumonia, duration of hospitalization, recovery rate of pneumonia, and the main secondary outcomes (including mortality of pneumonia, rate of ICU/hospital admission, complications rate, time to resolution of fever, and change in serum levels of serum PCT and hs-CRP), strengthening the hypothesis that low vitamin D status is a consequence of ill health rather than its cause.…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin D status is an independent risk factor for treatment failure and delayed recovery from severe lower respiratory infections. 52 The level of serum vitamin D in patients with pneumonia was significantly low, 53 maybe because of a systemic inflammatory response in the host. 54,55 In total, there remains little evidence to suggest that vitamin D supplementation has an effect on most outcomes, including time to resolution of pneumonia, duration of hospitalization, recovery rate of pneumonia, and the main secondary outcomes (including mortality of pneumonia, rate of ICU/hospital admission, complications rate, time to resolution of fever, and change in serum levels of serum PCT and hs-CRP), strengthening the hypothesis that low vitamin D status is a consequence of ill health rather than its cause.…”
Section: Discussionmentioning
confidence: 99%
“…Haugen J et al, and Oduwole OA et al, studies found that vitamin D deficiency is associated with treatment failure in severe pneumonia, present study also had similar predictor which was indirectly measured by clinical signs of rickets. 14,15 Studies have also shown low Vitamin D levels is an independent risk factor for the development of pneumonia and increases the disease severity. [16][17][18][19] Authors found that anemia and its increase in severity is risk factor for treatment failure, this result is comparable with study done by Moschovis PP et at, in which anemia at high altitude increases the risk of poor outcome with severe pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review seems to support the protective role of VD against tuberculosis, otitis media, pharyngotonsillitis, bronchiolitis, and viral wheezing . Low VD status (25(OH)D < 50 nmol/L) is an independent risk factor for treatment failure and delayed recovery from severe lower respiratory infections in children . Shen‐Hao Lai et al observed that infants with low cord serum 25(OH)D levels have poorer lung function at 6 months of age compared with those with high levels.…”
Section: Role Of Vd In Infectionsmentioning
confidence: 99%